Regulatory networks, legal federalism, and multi-level regulatory systems - Wolfgang Kerber; Julia Wendel (Philipps-University Marburg, School of Business and Economics, 2016)
Transnational regulatory networks play important roles in multi-level regulatory regimes, as e.g, the European Union. In this paper we analyze the role of regulatory networks from the perspective of the economic theory of legal federalism. Often sophisticated intermediate institutional solutions between pure centralisation and pure decentralisation can help to solve complex tradeoff problems between the benefits and problems of centralised and decentralised solutions. Drawing upon the insights of the political science literature about regulatory networks, we show that regulatory networks might be an institutional innovation that can fulfill a number of functions (rule-making, best practices and policylearning, effective enforcement, conflict resolution) that might allow for a better intermediate solution between centralised and decentralised regulatory powers. We apply our approach in three case studies to very different regulatory networks, the Body of European Regulators for Electronic Communication (BEREC), the European Competition Network (ECN), and the International Competition Network (ICN). An important result is that regulatory networks might not only be a temporary phenomenon but part of long-term institutional solutions in European multi-level regulatory regimes.
Keywords: K2; F55; H11; H77; 330; regulatory networks; multi-level regulatory systems; legal federalism; EU regulation